Digital Da'wah Innovation for Religious Moderation Programs at UIN Raden Intan Lampung - Syukur, Abdul; Saputra, Devid (KOMUNIKA, 2024)
This study examines the implementation of digital da'wah innovation in promoting religious moderation at the State Islamic University (UIN) Raden Intan Lampung. Using a qualitative approach with data collected through interviews with 15 key informants (consisting of university leaders, lecturers, and students), observations, and document analysis, this research explores how digital platforms are utilized to advance moderate religious understanding among the academic community. The findings reveal that UIN Raden Intan Lampung has successfully leveraged various digital channels, including social media platforms (Instagram, YouTube, TikTok, and X/Twitter), online webinars, and digital learning modules, to disseminate messages of religious moderation. The university's digital da'wah strategy integrates traditional Islamic values with modern digital communication approaches, making religious moderation more accessible and appealing to younger audiences. Despite challenges such as digital literacy gaps and online misinformation, the program has shown promising results in fostering interfaith dialogue and promoting inclusive religious perspectives. This study contributes to the growing literature on digital religious education and provides practical insights for other Islamic educational institutions seeking to implement similar programs in the digital age.